Audition and balance: The impact of echolocation on postural control - Chiraz Chouk; Léo Dross; Nicolas Termoz (PLoS ONE, 2025)
The links between the perception of acoustic signals and postural control remain largely unexplored, and the control models proposed to date have yet to assign these sensory inputs a role alongside visual, proprioceptive, and vestibular information. Research on this topic has produced varied conclusions, likely due to significant methodological differences. Our study makes novel contributions by aiming to determine the impact of the auditory system—specifically through the perception of echoes—on postural control during quiet standing and to identify the potential link between auditory perception and postural stability. To create controlled acoustic conditions, we developed an automated device representing a reflective object, positioned statically in two locations and dynamically moved in two directions relative to the participants. Eleven naive, blindfolded adult participants (mean age: 23 years ±2.2; mean height: 174 cm ±7.4) with normal hearing underwent kinematic (optoelectronic cameras) and kinetic (force plate) analyses in a semi-anechoic room. After each trial, participants reported their perception of the object’s presence, position, movement direction, and distance. Results demonstrated improved object perception and greater stability in dynamic conditions, particularly when the target moved towards the participants, compared to static conditions. However, no significant correlation between perception and postural stability was observed. Our findings suggest that acoustic information, especially through echo perception, could plays a role in postural control processes alongside visual, proprioceptive, and vestibular input. However, more controlled studies are necessary to examine the relationship between perception and postural stability.